Molecular mimicry and autoimmunity (2018)
Molecular mimicry is one of the leading mechanisms by which infectious or chemical agents may induce autoimmunity. It occurs when similarities between foreign and self-peptides favor an activation of autoreactive T or B cells by a foreign-derived antigen in a susceptible individual. However, molecular mimicry is unlikely to be the only underlying mechanism for autoimmune responses; other factors such as breach in central tolerance, non-specific bystander activation, or persistent antigenic stimuli (amongst others) may also contribute to the development of autoimmune diseases. Host genetics, exposure to microbiota and environmental chemicals are additional links to our understanding of molecular mimicry. Our current knowledge of the detailed mechanisms of molecular mimicry is limited by the issues of prolonged periods of latency before the appearance of disease, the lack of enough statistical power in epidemiological studies, the limitations of the potential role of genetics in human studies, the relevance of inbred murine models to the diverse human population and especially the limited technology to systematically dissect the human T-cell repertoire and B-cell responses. Nevertheless, studies on the role of autoreactive T-cells that are generated secondary to molecular mimicry, the diversity of the T-cell receptor repertoires of auto-reactive T-cells, the role of exposure to cryptic antigens, the generation of autoimmune B-cell responses, the interaction of microbiota and chemical adjuvants with the host immune systems all provide clues in advancing our understanding of the molecular mechanisms involved in the evolving concept of molecular mimicry and also may potentially aid in the prevention and treatment of autoimmune diseases. © 2018 The Authors